Antibacterial activity of the micro and nanostructures of the optical material tris(8-hydroxyquinoline)aluminum and its application as an antimicrobial coating. Issue 42 (23rd September 2022) - Saeed, Abdu; Madkhli, Aysh Y.; Pashameah, Rami Adel; Bataweel, Noor M.; Razvi, Mir Ali; Salah, Numan
Abstract : This research gives insight into the optical material tris(8-hydroxyquinoline)aluminum (Alq3 ) micro and nanostructures as an antimicrobial agent against different human pathogenic bacteria. In this work, Alq3 was applied as an antimicrobial coating. Abstract : Although tris(8-hydroxyquinoline)aluminum (Alq3 ), a fluorescent optical organometallic material, is known for its applications in optoelectronics, it has only few and limited applications in the biological field. In this study, the antibacterial activity of Alq3 micro and nanostructures was investigated. We prepared Alq3 nanostructures. We prepared nanosized Alq3 as rice-like structures that assembled into flower shapes with an α-crystal phase. Then, Alq3 micro and nanostructure antibacterial activities were estimated against seven human pathogenic bacterial strains. Besides, we compared their antibacterial activities with those of standard antibiotics. The minimal inhibitory concentration (MIC), minimum bactericidal concentration (MBC), and IC50 were evaluated. Alq3 micro and nanostructure antibacterial activity showed considerable values compared to standard antibiotics. Besides, the obtained data revealed that the antibacterial activity of Alq3 in nanostructures with a new morphology is more than that in microstructures. The antibacterial activity of Alq3 nanostructures was attributed to their more surface interactions with the bacterial cell wall. The molecules of 8-hydroxyquinoline in the Alq3 structure could play crucial roles in its antibacterial activity. To apply the achieved results, Alq3 was incorporated with polystyrene (PS) in a ratio of 2% to fabricate a PS/Alq3 composite and used to coat glass beakers, which showed inhibition in the bacterial growth reduced to 65% compared with non-coated beakers. The finding of this study showed that Alq3 could be used as a promising antimicrobial coating.